The Use of Activated Carbons with Basic Properties for the Treatment of 2-Chlorophenol - Amjad H. El-Sheikh; Alan P. Newman; Hafid K. Al-Daffaee; Suki S. Phull; Daniel E. Lynch (Adsorption Science & Technology)
A range of basic activated carbons was prepared from single cultivar Jordanian olive stones and their chemical composition, textural properties and surface groups investigated. One of the samples was de-ashed and then oxidized using concentrated nitric acid to study the effects of inorganic content and surface oxidation on its adsorption capacity towards 2-chlorophenol (2-CP). Commercial samples with combined acidic and basic properties were also tested with respect to 2-CP adsorption. An attempt was made to correlate the total basicity with the adsorption constants of the Langmuir equation and with other properties. These properties included burn-off, apparent surface area, micropore volume, total pore volume and Methylene Blue (MB) adsorption surface area. The total basicity had no relationship with any adsorption parameter. However, total basicity was found to have a relationship with the total pore volume, the micropore volume, MB adsorption and burn-off. The BET surface area showed only a very weak relationship with the total basicity. Burn-off had a relationship with the relative affinity of the adsorbate and the surface and Langmuir constants, but not with the adsorption capacity. De-ashing the sample using HF/HCl decreased the total basicity and MB adsorption but increased the total acidity and the capacity towards 2-CP uptake. The mineral contents of both prepared and commercial samples were analyzed and found to play no role in the adsorption of 2-CP.